2010
DOI: 10.1007/s10529-010-0250-8
|View full text |Cite
|
Sign up to set email alerts
|

Increasing anthraquinone production by overexpression of 1-deoxy-d-xylulose-5-phosphate synthase in transgenic cell suspension cultures of Morinda citrifolia

Abstract: A Morinda citrifolia cell line was obtained by overexpresion of 1-deoxy-D: -xylulose 5-phosphate synthase (DXS) from Catharanthus roseus, a key enzyme of the metabolic pathway of anthraquinones (AQs). This cell line increased AQs production by about 24% compared to the control cell line. This transgenic cell line which carries dxs cDNA isolated from Catharanthus roseus, was achieved by direct transformation of cell suspension cultures of M. citrifolia using a hypervirulent Agrobacterium tumefaciens strain. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…It was found that over-expression of AtDXS in Daucus carota resulted in remarkably higher accumulation of both carotenoids and chlorophylls (Simpson et al 2016). Similar results were also obtained in T. wilfordii (Zhang et al 2019), C. roseus (Peebles et al 2011), and other plants (Augustin et al 2015;Kai et al 2011;Morris et al 2006;Muñoz-Bertomeu et al 2006;Quevedo et al 2010;Vaccaro et al 2019). In addition, due to the bacteriostatic and bactericidal effects of terpenoids (Gershenzon and Dudareva 2007), the increase of terpenoid content may help plants resist to pathogens.…”
Section: Over-expression and Co-expression Regulation Of Dxs In Plantssupporting
confidence: 55%
“…It was found that over-expression of AtDXS in Daucus carota resulted in remarkably higher accumulation of both carotenoids and chlorophylls (Simpson et al 2016). Similar results were also obtained in T. wilfordii (Zhang et al 2019), C. roseus (Peebles et al 2011), and other plants (Augustin et al 2015;Kai et al 2011;Morris et al 2006;Muñoz-Bertomeu et al 2006;Quevedo et al 2010;Vaccaro et al 2019). In addition, due to the bacteriostatic and bactericidal effects of terpenoids (Gershenzon and Dudareva 2007), the increase of terpenoid content may help plants resist to pathogens.…”
Section: Over-expression and Co-expression Regulation Of Dxs In Plantssupporting
confidence: 55%
“…In contrast, the most highly expressed enzyme in the MEP pathway was the terminal enzyme HDR (1-hydroxy-2-methyl-butenyl 4-diphosphate reductase), which catalyzes the formation of isopentenyl diphosphate (IPP) and its isomer, dimethylallyl diphosphate (DMAPP). Anthraquinone production is increased by the overexpression of 1-deoxy-D: -xylulose-5-phosphate synthase (DXS) in Morinda citrifolia cells [44]. In Polygonum, DXS had the lowest expression (RPKM 12.2) compared to the genes coding the downstream enzyme ( Figure 4B).…”
Section: Genes Involved In Secondary Metabolismmentioning
confidence: 99%
“…It has been reported that the overexpression of DXS in Arabidopsis led to an increase in terpenoid concentrations (Estévez et al, 2001). Overexpression of DXS in transgenic cell-suspension cultures of Morinda citrifolia increases anthraquinone production (Quevedo et al, 2010). These results suggest that the overexpression of DXS can increase secondary metabolic concentrations; however, cloning and analysis of the DXS gene are important prerequisites.…”
Section: Discussionmentioning
confidence: 98%
“…In Catharanthus roseus hairy roots, the expression of DXS and geraniol-10-hydroxylase or anthranilate synthase increases accumulation of the terpenoid indole alkaloid (Peebles et al, 2011). In addition, overexpression of DXS increases anthraquinone production in transgenic cell-suspension cultures of Morinda citrifolia (Quevedo et al, 2010).…”
Section: Introductionmentioning
confidence: 99%